Efektivitas Gel Ekstrak Etanol Daun Bakung (Crinum Asiaticum L.) Terhadap Luka Pada Model Tikus Diabetes - Inggried Audrey; Astriani Natalia Br Ginting; Finna Piska (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Diabetes is a metabolic disease caused by hyperglycemia, often accompanied by chronic skin lesions. Wounds occur due to infections that appear on the skin. Daffodils have been used by the community as medicine, which is usually used to heal bruises, low back pain, fractures, and antidiabetics. Daffodils contain secondary metabolites such as alkaloids, flavonoids, saponins and terpenoids. Each compound has a specific mechanism in the healing of diabetic wounds. This study aims to determine the effect of giving daffodil ethanol extract gel in the healing of wounds in male rat models of diabetes. This research method in vivo used induced male rats with an allexone of 120mg/kgBB. The treatment in rats was divided into 6 treatments, namely normal, negative control, positive control, GEDB 5%, GEDB 10%, GEDB 15%. This study was carried out for 14 days with gel application twice a day. The results of the study showed that 5% Lily Leaf Extract Gel showed complete wound healing in rats. The concentrations of GEDB of 5% and 10% turned out to be almost as effective as chloramphenicol cream, where the wound was completely closed on the 14th day and the healing rate was quite high. The conclusion obtained is that Lily Leaf Extract Gel can treat diabetic wounds in rats.